THE METHOD OF ANALYSIS AND PERFORMANCE MANAGEMENT OF DISPERSED PRODUCTION PLANNING - Pavlenko, Petro; Khlevnyy, Andriy (Proceedings of National Aviation University, 2014)
The article presents a calculation method of management index, and offers a calculation model of the required number of experts for effective production planning. There was created a method of analysis and performance management of dispersed production planning